2014
DOI: 10.1136/acupmed-2013-010484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Acupuncture and Auricular Acupressure in a Child with Trismus as a Sequela of Medulloblastoma

Abstract: In several countries the most common cause of death in young people is cancer. Patients with head and neck cancer often have complications after cancer treatment. Radiation therapy can cause oral trismus, which is related to high doses of radiation. Although acupuncture is reported to be effective and is widely used for the treatment of peripheral facial paralysis by promoting an improvement of motor functions, few reports in the literature demonstrate its effectiveness. We report a case in which the symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
8
0
4
Order By: Relevance
“…However, the auriculotherapy is a type of acupuncture that consists in a nonpharmacological technique, which has an anxiety‐reducing effect . Auricular acupuncture is minimally invasive, easily accessible therapy and has shown to reduce general and preoperative anxiety . In the present case report, the auriculotherapy using Shenmen and Brainstem points was effective for the control of anxiety.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, the auriculotherapy is a type of acupuncture that consists in a nonpharmacological technique, which has an anxiety‐reducing effect . Auricular acupuncture is minimally invasive, easily accessible therapy and has shown to reduce general and preoperative anxiety . In the present case report, the auriculotherapy using Shenmen and Brainstem points was effective for the control of anxiety.…”
Section: Discussionmentioning
confidence: 58%
“…We compared the efficacy of auriculotherapy in relation to intranasal midazolam medication and both treatments reduced anxiety after 30 minutes . However, the auriculotherapy is a type of acupuncture that consists in a nonpharmacological technique, which has an anxiety‐reducing effect . Auricular acupuncture is minimally invasive, easily accessible therapy and has shown to reduce general and preoperative anxiety .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that researched acupuncture as an alternative means for pediatric diseases found that it is safe, feasible, and acceptable [ 93 99 ]. One study explored acupuncture as an effective therapy of pain relief for children and adolescents after tonsillectomy [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acupressure at ST36 (Zusanli) acupoint improve a patient's comfort in colorectal cancer 149 . AA with laser acupuncture plays a significant role in preventing the spasm of jaw muscle and facial paralysis following cancer therapy 150 . Acupressure with magnetic sticker improved the digestive functions and quality of sleep in gastro enteric tumour patients 151 …”
Section: Acupressure Applicationsmentioning
confidence: 99%